Manajemen Pembelajaran Bahasa Arab Berbasis TIK di Madrasah Aliyah Daarul Uluum Majalengka - Badrudin, Badrudin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2017)
Abstract This study aimed to analyze the management of ICT-based Arabic learning. This study was designed to find the management of ICT-based Arabic learning in MA Daarul Uluum Majalengka. This study proposed that the integration of various fields of studies with ICT, including Arabic language learning, is undeniably vital to be enhanced in this digital era. However, the constraints experienced by some institutions, especially the educators, have not had a clear format of the use of ICT in the integration effort of the both disciplines. This study applied a qualitative research approach. The research method was descriptive method. The data were collected by conducting observation, interview, and documentation. The data were analyzed using the techniques qualitative analysis. The results showed that the design of ICT-based Arabic learning model can be developed at MA Daarul Uluum Majalengka a communicative computer-based Arabic learning model. The materials and other learning tools are designed using a computer program. Through this kind of learning models, a teacher served as learning motivator and facilitator elaborating the materials that need clarification for the learners. Keywords : management, Arabic learning, information communication technologies